To rewrite the sine function \( f(x) = -2\sin(x - \pi) + 3 \) as a cosine function, we can use the relationship between sine and cosine.
Recall the identity: \[ \sin(x - \pi) = -\cos(x) \] This is because sine and cosine are phase-shifted by \( \frac{\pi}{2} \) (or \( 90^\circ \)). Specifically, given that \(\sin(\theta) = \cos\left(\theta - \frac{\pi}{2}\right)\), we can express sine in terms of cosine.
Thus, we can rewrite the sine term in the function as follows:
- Substitute \( \sin(x - \pi) \) with \(-\cos(x)\): \[ f(x) = -2(-\cos(x)) + 3 = 2\cos(x) + 3 \]
So, the function in terms of cosine becomes: \[ f(x) = 2\cos(x) + 3 \]
Summary:
The sine function \( f(x) = -2\sin(x - \pi) + 3 \) is rewritten as \( f(x) = 2\cos(x) + 3 \) by using the identity that relates sine and cosine, specifically recognizing that \( \sin(x - \pi) = -\cos(x) \).